Bio-inspired colorimetric detection of mercury ions using dna functionalized gold nanoparticles - Parekh, Kirit Vijaykumar. (2010)
This report presents a systematic study on the feasibility of using oligonucleotide functionalized gold nanoparticles (AuNPs) for detection of mercury ions (Hg2+). AuNPs are chosen for their unique size dependent optical properties, which enables visual observation. Oligonucleotide probes were deliberately designed with incorporated T-T base mismatches to exploit the unique Thymine-Hg2+-Thymine (T-Hg2+-T) coordination chemistry. AuNPs were synthesized according to Turkevich’s method and then functionalized separately with the six thiol terminated oligonucleotides. These three sensing systems, oligo1/oligo2-AuNPs (4 T-T mismatches), oligo3/oligo4-AuNPs (6 T-T mismatches) and oligo5/oligo6-AuNPs (8 T-T mismatches) were treated with varying concentrations of Hg2+ ions. Results were analyzed using Scanning Electron Microscopy (SEM), Ultraviolet-Visible Spectroscopy (UV-Vis), Fourier Transform Infrared Spectroscopy (FTIR) and visually. In general, addition of Hg2+ ions led to the aggregation of the AuNPs as seen in the SEM. These results were coherent with the red-shift observed in the UV-Vis spectra and the colour change of the solution from red to blue-grey. The plot of absorption ratio (A700/A520) showed a sensitive function towards the [Hg2+]. Oligo1/Oligo2-AuNP sensing system displayed a linear range of 0-350 nM and a low detection limit of 61 nM. The preliminary results from the other sensing system imply that by varying the number of T-T mismatches, the linear detection range can be tuned and be used accordingly. Nonetheless, a simple bio-inspired colorimetric sensor which is cheap, fast and easy to use has been successfully designed for Hg2+ detection.